GGC Repeat Expansion of NOTCH2NLC in Taiwanese Patients With Inherited Neuropathies. (11th January 2022) - Liao, Yi-Chu; Chang, Fu-Pang; Huang, Han-Wei; Chen, Ting-Bing; Chou, Ying-Tsen; Hsu, Shao-Lun; Jih, Kang-Yang; Liu, Yi-Hong; Hsiao, Cheng-Tsung; Fukukda, Hiromi; Mizuguchi, Takeshi; Lin, Kon-Ping; et al.
Abstract : Background and Objectives: The GGC repeat expansion in the 5′ untranslated region of NOTCH2NLC was recently identified as the cause of neuronal intranuclear inclusion disease (NIID), which may manifest with peripheral neuropathy. The aim of this study is to investigate its contribution to inherited neuropathy. Methods: This cohort study screened patients with molecularly undiagnosed Charcot-Marie-Tooth disease (CMT) and healthy controls for the GGC repeat expansion in NOTCH2NLC using repeat-primed PCR and fragment analysis. The clinical and electrophysiologic features of the patients harboring the GGC repeat expansion were scrutinized. Skin biopsy with immunohistochemistry staining and electric microscopic imaging were performed. Results: One hundred twenty-seven unrelated patients with CMT, including 66 cases with axonal CMT (CMT2), and 200 healthy controls were included. Among them, 7 patients with CMT carried a variant NOTCH2NLC allele with GGC repeat expansion, but it was absent in controls. The sizes of the expanded GGC repeats ranged from 80 to 104 repeats. All 7 patients developed sensory predominant neuropathy with an average age at disease onset of 37.1 years (range 21–55 years). Electrophysiologic studies revealed mild axonal sensorimotor polyneuropathy. Leukoencephalopathy was absent in the 5 patients who received a brain MRI. Skin biopsy from 2 patients showed eosinophilic, ubiquitin- and p62-positive intranuclear inclusions in the sweat gland cells and dermal fibroblasts. Two of the 7 patients had a family history of NIID. Discussion: The NOTCH2NLC GGC repeat expansions are an underdiagnosed and important cause of inherited neuropathy. The expansion accounts for 10.6% (7 of 66) of molecularly unassigned CMT2 cases in the Taiwanese CMT cohort. Classification of Evidence: This study provides Class III evidence that in Taiwanese patients with genetically undiagnosed CMT, 10.6% of the CMT2 cases have the GGC repeat expansion in NOTCH2NLC .